Project MENTOR+ : Mentor-led exercise with cognitive-behavioral therapy to improve perceived competence, reduce social anxiety, and increase physical activity in overweight adolescents. - Carraway, Marissa (East Carolina University, 2014)
Overweight adolescents are at increased risk for peer victimization and avoidance of physical activity, thus perpetuating overweight status and peer victimization. Avenues of intervention include (1) reducing avoidance through increased perceived competence for physical activity and (2) bolstering protective factors including familial support and problem-focused coping to minimize the negative impact of victimization. The purpose of the current pilot study was to assess an intervention designed to improve perceived competence for activity through mentor-led exercise and improve perceived social support and problem-focused coping skills through group-based skills training. The present pilot study, a randomized clinical trial with waitlist control, examined the impact of MENTOR alone versus MENTOR+CBT on physical and psychological outcomes at post treatment (12 weeks) and 4-month follow-up (28 weeks). Twenty-four overweight Caucasian and African American adolescents were assigned either to MENTOR (n = 11) or MENTOR+CBT (n = 13). All participants completed the Physical Appearance Related Teasing Scale, the Children and Youth Physical Self-Perception Profile, and accelerometry. The MENTOR+CBT group also completed the Social Anxiety Scale for Adolescents and Multidimensional Scale of Perceived Social Support. Repeated measures Analysis of Variance revealed a statistically significant change in perceived athletic competence by time, F(2, 44) = 4.32, p = .019, [eta][subscript]p² = .164. However, this did not result in significant changes in physical activity across time, F(2, 46) = 1.846, p = .169, [eta][subscript]p² = .074. There were no statistically significant changes in social anxiety or perceived social support nor were there differences in outcomes by group. While findings did not support the hypothesis that mentor-led exercise plus group-based skills training would improve social anxiety and social support as well as increase physical activity beyond the exercise program alone, differences in outcomes by ethnicity and a floor effect due to low baseline scores on psychosocial measures limit interpretation of these findings. Additional randomized clinical trials which include adolescents experiencing weight-related teasing and control for ethnicity are needed to compare both levels of treatment with control and more accurately determine the value of this intervention.
Keywords: Psychology; Health sciences; Kinesiology; Cognitive-behavioral; Pediatric obesity; Peer victimization; Physical activity; Weight; Mentoring; Exercise--Psychological aspects; Overweight teenagers; Discrimination against overweight persons; Exercise for youth